1966
DOI: 10.1159/000457206
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Lactic Dehydrogenase in Hematologic and Neoplastic Disease

Abstract: Determinations of lactic dehydrogenase (LDH), LDH isoenzymes (by heat fractionation) and alpha-hydroxybutyrate dehydrogenase (HBD, the equivalent of LDH5) were performed on the bone marrow blood of patients with various hematological and neoplastic disorders. In the majority of patients, bone marrow LDH activity was higher than corresponding serum LDH activity. Marrow LDH was higher than control values only in those disorders where serum LDH was elevated ; (megaloblastic anemia, sickle cell anemia, chronic mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…However, further research is needed to explore why CK-MB elevation occurs in breast cancer with distant metastasis and whether elevated CK-MB originates from tumors or other sources. α-HBDH, as an LDH isoenzyme, is significantly elevated in the serum of some malignant tumor patients and is associated with the prognosis of malignant tumors ( 25 27 ). The combined application of α-HBDH, CEA, and CA125 in the early diagnosis of breast cancer has been found to be valuable ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, further research is needed to explore why CK-MB elevation occurs in breast cancer with distant metastasis and whether elevated CK-MB originates from tumors or other sources. α-HBDH, as an LDH isoenzyme, is significantly elevated in the serum of some malignant tumor patients and is associated with the prognosis of malignant tumors ( 25 27 ). The combined application of α-HBDH, CEA, and CA125 in the early diagnosis of breast cancer has been found to be valuable ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma and serum from blood sources other than the peripheral blood have not been examined for their effect on lymphocyte reactivity. The effect of bone marrow plasma on lymphocyte reactivity was examined in this study because bone marrow-derived serum has been shown to differ from peripheral blood serum obtained from the same donor with respect to levels of enzymes (Elliot & Fleming 1965, Spector et al 1966, Chua et al 1970, Hoch-Ligeti & Jarsen 1976, cell growth activators (Burger & Knyszynski 1969, Knyszynski & Burger 1971 and inhibitors (Zoumbos et al 1985, Lindemann et al 1989 in patients with other haematological and neoplastic diseases including myeloid leukaemia, and because of its localized influence on cells present in the bone marrow environment. Plasma was selected for this study rather than serum because platelets are the source of a potent mitogen present in serum but not in plasma (Gospodarowicz & I11 1980, Antoniades 1981.…”
mentioning
confidence: 99%
“…However, further research is needed to explore why CK-MB elevation occurs in breast cancer with distant metastasis and whether elevated CK-MB originates from tumors or other sources. a-HBDH, as an LDH isoenzyme, is significantly elevated in the serum of some malignant tumor patients and is associated with the prognosis of malignant tumors (25)(26)(27). The combined application of a-HBDH, CEA, and CA125 in the early diagnosis of breast cancer has been found to be valuable (28).…”
Section: B Amentioning
confidence: 99%